The Afro-American Realty Company - Osofsky, Gilbert (The Harlem reader: a celebration of New York's most famous neighborhood, from the renaissance years to the twenty-first century, 2003)
An anthology of fiction, nonfiction, memoir, poetry, and other narratives provides a portrait of Harlem at diverse points in its history, from the early days through the Harlem Renaissance to the present day.
OCLC: 50810395
Keywords: Business History and race